2015
DOI: 10.1038/ncomms6939
|View full text |Cite
|
Sign up to set email alerts
|

A dynamically coupled allosteric network underlies binding cooperativity in Src kinase

Abstract: Protein tyrosine kinases are attractive drug targets because many human diseases are associated with deregulation of kinase activity. However, how the catalytic kinase domain integrates different signals and switches from an active to an inactive conformation remains incompletely understood. Here we identify an allosteric network of dynamically coupled amino acids in Src kinase that connects regulatory sites to the ATP- and substrate-binding sites. Surprisingly, reactants (ATP and peptide substrates) bind with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(135 citation statements)
references
References 64 publications
12
120
0
Order By: Relevance
“…For example, in agreement with previous studies, we observed that both PKC and PKA show positive cooperativity between substrate and ATP binding (43). We posit that it is likely not a universal kinase mechanism as a recent paper (44) found that negative cooperativity is observed in the tyrosine kinases Src, Abl, and Hck. Although the negative cooperativity could stem from differences between kinase families, an important autoinhibitory mechanism for both PKC and PKA is pseudosubstrate binding.…”
Section: Journal Of Biological Chemistry 21967supporting
confidence: 79%
“…For example, in agreement with previous studies, we observed that both PKC and PKA show positive cooperativity between substrate and ATP binding (43). We posit that it is likely not a universal kinase mechanism as a recent paper (44) found that negative cooperativity is observed in the tyrosine kinases Src, Abl, and Hck. Although the negative cooperativity could stem from differences between kinase families, an important autoinhibitory mechanism for both PKC and PKA is pseudosubstrate binding.…”
Section: Journal Of Biological Chemistry 21967supporting
confidence: 79%
“…In a recent work on Src kinase, Foda et al show a negative binding cooperativity between ATP and substrates(Foda et al, 2015); while a positive cooperativity was measured for ADP and phosphorylated substrate. These authors found that the negative cooperativity is mediated by an allosteric network of contacts initiated by a protonation event occurring at the DFG loop (Foda et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These authors found that the negative cooperativity is mediated by an allosteric network of contacts initiated by a protonation event occurring at the DFG loop (Foda et al, 2015). This contrasts the positive K- type binding cooperativity found for PKA-C (Masterson et al, 2008), where a high degree of cooperativity was observed for ATP with the endogenous protein kinase inhibitor (PKI), regulatory subunits (R-subunits), (Herberg and Taylor, 1993) and substrates (Kim et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…These structures provide important insights into the binding mode of the pyrazine macrocycles and how they achieve specificity for Src kinase. However, the structural basis of the nitrophenylalanine macrocycles’ ability to inhibit Src kinase as well as the activating “gatekeeper” mutant (Thr338Ile) of Src (Azam et al, 2008; Foda et al, 2015) while maintaining selectivity remained unknown. Pharmacological inhibition of the Src gatekeeper mutant is of particular interest since the analogous mutation in other kinases frequently underlie drug resistance in the clinic, and few kinase inhibitors are active against this mutation.…”
Section: Introductionmentioning
confidence: 99%